2012
DOI: 10.24034/j25485024.y2012.v16.i3.2331
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kompetensi Sumber Daya Manusia Terhadap Kinerja Pegawai KPPBC Tipe Madya Pabean Tanjung Perak Surabaya

Abstract: This research aims to analyze the extent to which communication skills, teamwork, leadership and disconnection opinion affect employee performance of KPPBC Customs Office Middle Type Tanjung Perak Surabaya. The total population is 334 people who are employees KPBBC Customs Office Middle Type Tanjung Perak Surabaya. The Object of this study is 25% of the population that is as much as 83 respondents. The analyzes were performed using multiple linear regression analysis were used to prove the effect of independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
1
2
0
5
Order By: Relevance
“…Thus the sixth hypothesis (H6) is accepted. The results of this study are in line with previous studies, namelyYunus (2012);Klarner, et al,…”
supporting
confidence: 94%
See 1 more Smart Citation
“…Thus the sixth hypothesis (H6) is accepted. The results of this study are in line with previous studies, namelyYunus (2012);Klarner, et al,…”
supporting
confidence: 94%
“…Klarner, et al, 2013 have revealed that, it is very necessary for human resources who have adequate competence because competence is a key factor in improving employee performance. Yunus, 2012 andRudlia, 2016 revealed that employee performance is strongly influenced by competence. Competence is something that is measurable, can be observed, predicted, and evaluated which is reflected in one's work behavior.…”
Section: Competencementioning
confidence: 99%
“…Oleh karena itu diperlukan sumberdaya manusia yang memiliki kompetensi memadai karena kompetensi merupakan faktor kunci dalam meningkatkan prestasi kerja pegawai (Klarner, et al, 2013). Penelitian sebelumnya membuktikan adanya pengaruh positif antara kompetensi terhadap kinerja pegawai (Yunus, 2012dan Rudlia, 2016. Penelitian oleh Dhermawan, dkk.…”
Section: Pendahuluan Latar Belakang Masalahunclassified
“…Dengan melakukan pengelolaan SDM yang baik, maka akan menghasilkan output yang baik pula bagi perusahaan (Markos dan Sridevi 2010). Walaupun didukung dengan sarana dan prasarana serta sumber dana yang berlebihan, tanpa dukungan SDM yang handal, pelaksanaan kegiatan tidak akan terselesaikan dengan baik (Yunus 2012). Selain itu, berdasarkan hasil rekapitulasi data sistem aplikasi keuangan, dapat diketahui bahwa masih terdapat beberapa unit kerja di IPB yang belum melakukan input data transaksi keuangan ke dalam sistem aplikasi keuangan secara tepat waktu (Gambar 1 dan Gambar 2).…”
Section: Pendahuluanunclassified